Biological soil attributes in oilseed crops irrigated with oilfield produced water in the semi-arid region - Meneses, Ana Clarice; Weber, Olmar; Crisóstomo, Lindbergue; Andrade, Denis (Revista Ciência Agronômica, 2016)
Wastewater from oil is the main residue of the oil industry. Studies have shown that wastewater, or produced water, can be treated and used as an alternative source for the irrigation of oilseed crops. The aim of this work was to evaluate the effect of treated produced water on the biological properties of soil cultivated with the castor bean cv. BRS Energy and the sunflower cv. BRS 321 respectively, for two and three successive cycles of grain production. The first cycle in the sunflower and castor bean corresponds to the dry season and the second cycle to the rainy season. The third crop cycle in the sunflower relates to the dry season. The research was carried out from August 2012 to October 2013, in the town of Aracati, in the State of Ceará (Brazil), where both crops were submitted to irrigation with filtered produced water (FPW), produced water treated by reverse osmosis (OPW), or groundwater water from the Açu aquifer (ACW), and to no irrigation (RFD). The treatments, with three replications, were evaluated during the periods of pre-cultivation and plant reproduction for soil respiration (Rs), total organic carbon (TOC) and the population density of bacteria (Bact) and filamentous fungi (Fung) in the soil. In the sunflower crop, these soil attributes are sensitive to the irrigation water used. Irrigation of the castor bean affects soil respiration. Under the conditions of this study, irrigation with FPW may be a short-term alternative in the castor bean and sunflower crops.